Sponge cake microstructure, starch retrogradation and quality changes during frozen storage - Díaz-Ramírez, Mayra (2016)
The effect of frozen storage (6 months) on the microstructure (microscopy, flatbed scanning and image analysis), quality (texture, moisture and specific volume) and starch retrogradation of the cake crumb were evaluated. After 2 months of storage, texture (firmness, cohesiveness and resilience) was significantly (P < 0.05) affected and starch retrogradation was observed, while by the fourth month, the crystallinity increased and crumb fractures were noticeable. Additionally, the shrinkage of starch granules was observed as the starch circularity (Sc) values significantly decreased (P < 0.05) by the sixth month of storage. Although structural changes were not detected by image analysis, it was demonstrated that cake microstructure damage is related to physical changes because the Sc was significantly correlated (P < 0.05) with moisture and specific volume and therefore with the cake quality and texture. Moreover, sugar re-crystallisation occurred during frozen storage, and it was significantly correlated (P < 0.05) with the deterioration in cake quality.